Paternal aging and increased risk of congenital disease, psychiatric disorders, and cancer - Conti, Simon L (Asian J Androl, 2016)
As couples are increasingly delaying parenthood, the effect of the aging men and women on reproductive outcomes has been an area of increased interest. Advanced paternal age has been shown to independently affect the entire spectrum of male fertility as assessed by reductions in sperm quality and fertilization (both assisted and unassisted). Moreover, epidemiological data suggest that paternal age can lead to higher rates of adverse birth outcomes and congenital anomalies. Mounting evidence also suggests increased risk of specific pediatric and adult disease states ranging from cancer to behavioral traits. While disease states associated with advancing paternal age have been well described, consensus recommendations for neonatal screening have not been as widely implemented as have been with advanced maternal age.